A National Survey of Canadian Psychiatrists' Attitudes toward Medical Assistance in Death. (November 2017) - Rousseau, Skye; Turner, Sarah; Chochinov, Harvey Max; Enns, Murray W.; Sareen, Jitender
Background: Bill C-14 allows for medical assistance in dying (MAID) for patients who have intolerable physical or psychological suffering that occurs in the context of a reasonably foreseeable death. In Canada, psychiatrist support for MAID on the basis of mental illness and beliefs influencing level of support are unknown. The objectives of this research were to 1) determine if psychiatrists are supportive of MAID under certain conditions and on the basis of mental illness and 2) determine what factors are related to psychiatrist support for MAID on the basis of mental illness. Methods: This cross-sectional study was conducted among 528 psychiatrists in Canada using an online survey platform (February 19 to March 11, 2016). Results: The response rate was 20.9% ( n = 528). Most psychiatrists supported the legalisation of MAID in some circumstances (72%); however, only 29.4% supported MAID on the basis of mental illness. Factors correlating with decreased support for MAID for mental illness were the belief that MAID for mental illness would change the psychiatrists' commitment to their patients through enduring suffering, having a personal faith, and having had past patients who would have received MAID for mental illness were it legal but instead went on to recover. Interpretation: This study found that most psychiatrists do not support the legalisation of MAID for mental illness, despite being quite supportive of MAID in general. Objections seemed to be based upon concern for vulnerable patients, personal moral objections, and concern for the effect it would have on the therapeutic alliance.